Comprehensive comparison of three techniques for the treatment of adjacent segment degeneration after lumbar fusion - Li, Tao; He, Hang; Zhang, Tonghui; Li, Xugui; Xie, Wei; Huang, Biwang; Xu, Feng; Xiong, Chengjie (Frontiers in Surgery, 2023)
Purpose Adjacent segment disease(ASD) following lumbar fusion is technically challenging for spine surgeons. Posterolateral open fusion surgery with pedicle screw fixation is an effective way to treat symptomatic ASD with favorable clinical outcomes; however, it is associated with an increased morbidity rate. Therefore, minimally invasive spine surgery(MISS) is advocated. This study was designed to compare clinical outcomes among patients with symptomatic ASD who underwent percutaneous transforaminal endoscopic discectomy(PTED) with transforaminal approach and posterior lumbar interbody fusion(PLIF) with cortical bone trajectory screw fixation(CBT-PLIF), and PLIF with traditional trajectory screw fixation(TT-PLIF). Results The operation time, incision length, intraoperative blood loss, and time to return to work in the PTED group were significantly decreased compared with the other two groups (P<0.05). The radiological indicators in the CBT-PLIF group and TT-PLIF group had better biomechanical stability compared with the PTED groups at the latest follow-up(P<0.05). The VAS of back pain in the CBT-PLIF group were significantly decreased compared with the other two groups at the latest follow-up(P<0.05). The good-to-excellent rate was 82.35% in the PTED group and 88.89% in the CBT-PLIF group, and 85.00% in the TT-PLIF group. No serious complications were encountered. Two patients experienced dysesthesia in the PTED group; Screw malposition was found in one patient in the CBT-PLIF group. One case with dural matter tear was observed in the TT-PLIF group. Conclusion All three approaches can treat patients with symptomatic ASD efficiently and safely. Functional recovery was more accelerated in the PTED group compared with the other approaches in the short term; CBT-PLIF and TT-PLIF can provide superior biomechanical stability to the lumbosacral spine following decompression compared with PTED, but compared with TT-PLIF, CBT-PLIF can significantly reduce back pain caused by iatrogenic muscle injury and improve functional recovery. Therefore, superior clinical outcomes were achieved in the CBT-PLIF group compared with the PTED group and the TT-PLIF in the long term.